Phytochemical Content Analysis of Simplex and Ethanol Extract of Pandanus amaryllifolius Roxb. Leaves as Potential Natural Ingredients - Ayu Nurhalimah; Nikadek Alya Saraswati Dewi; Tara Nia Shalma Nugraha; Anjelika Mesa Putri; Desiva Muspita Ayu; Resi Nopribulin; Iin Vita Noprianti (JURNAL LENTERA ILMIAH KESEHATAN, 2026)
This study aimed to compare the secondary metabolite profiles of crude drug (simplicia) and refluxed ethanol extract of Pandanus amaryllifolius Roxb. leaves through qualitative phytochemical screening. Fresh fragrant pandan leaves were processed into dried simplicia, powdered, and extracted using the reflux method with 96% ethanol (1:10 w/v) at ±78°C for 3 hours. The extract was concentrated using a rotary evaporator and analyzed for alkaloids, flavonoids, phenolics, saponins, terpenoids, and steroids based on standard color reactions and precipitate formation. The drying process resulted in a weight loss of 37.58%, indicating effective moisture removal, while extraction yielded 9% thick extract. Phytochemical screening revealed the presence of alkaloids, flavonoids, and terpenoids in both simplicia and extract, whereas phenolics, saponins, and steroids were not detected under the applied conditions. These findings indicate that 96% ethanol reflux extraction effectively isolates polar and semi-polar bioactive compounds without significant thermal degradation. The results provide a scientific basis for the development of pandan-based phytopharmaceuticals and natural cosmetic formulations.